The Influence of Work Discipline, Work Environment and Work Motivation on Employee Performance Through Job Satisfaction in Employees of Perumda Tirtanadi Medan - Fitri Dwiana; Prihatin Lumbanraja; R. Hamdani Pasaribu (Indonesian Journal of Business Analytics, 2025)
Employee performance is a key element in determining the success of an organization, especially in regional companies engaged in public services such as PERUMDA Tirtanadi Medan. As a provider of clean water services for the people of Medan City and its surroundings, the quality and continuity of service are highly dependent on the effectiveness and efficiency of its employees. Employee performance at PERUMDA Tirtanadi Medan is not optimal, indicated by many employees who still get sufficient, moderate and poor scores in the annual performance assessment. Suboptimal performance at PERUMDA Tirtanadi Medan has disrupted clean water services to the community, increased customer complaints, and decreased public trust in the quality of the company's services. Employees who have optimal performance can encourage the achievement of organizational goals. Many factors cause decreased performance, including work discipline, work environment, work motivation and job satisfaction. This study aims to determine the effect of work discipline and work motivation on employee performance mediated by job satisfaction. This research was conducted on 154 non-leadership employees at PERUMDA Tirtanadi Medan. Data analysis used in this research is outer model and inner model with SmartPLS software. The results revealed that the factor that most influences the performance of PDAM Tirtanadi Medan employees is employee motivation, the second is the work environment, the third is work discipline and the last mediating factor is job satisfaction. Furthermore, the factors that most influence job satisfaction of PDAM Tirtanadi Medan employees are work environment, second work motivation, and third work discipline. For mediating factors that most affect employee performance through job satisfaction of PDAM Tirtanadi Medan employees, namely work motivation, second work discipline, and the third is the employee work environment.